Radio imaging observations of PSR J1023+0038 in an LMXB state - Deller, A.; Moldon, J.; Miller-Jones, James; Patruno, A.; Hessels, J.; Archibald, A.; Paragi, Z.; Heald, G.; Vilchez, N. (IOP PUBLISHING LTD, 2015)
The transitional millisecond pulsar (MSP) binary system PSR J1023+0038 re-entered an accreting state in 2013 June in which it bears many similarities to low-mass X-ray binaries (LMXBs) in quiescence or near-quiescence. At a distance of just 1.37 kpc, PSR J1023+0038 offers an unsurpassed ability to study low-level accretion onto a highly magnetized compact object. We have monitored PSR J1023+0038 intensively using radio imaging with the Karl G. Jansky Very Large Array, the European VLBI Network and the Low Frequency Array, seeing rapidly variable, flat spectrum emission that persists over a period of six months. The flat spectrum and variability are indicative of synchrotron emission originating in an outflow from the system, most likely in the form of a compact, partially self-absorbed jet, as is seen in LMXBs at higher accretion rates. The radio brightness, however, greatly exceeds extrapolations made from observations of more vigorously accreting neutron star LMXB systems. We postulate that PSR J1023+0038 is undergoing radiatively inefficient "propeller-mode" accretion, with the jet carrying away a dominant fraction of the liberated accretion luminosity. We confirm that the enhanced ?-ray emission seen in PSR J1023+0038 since it re-entered an accreting state has been maintained; the increased ?-ray emission in this state can also potentially be associated with propeller-mode accretion. Similar accretion modes can be invoked to explain the radio and X-ray properties of the other two known transitional MSP systems XSS J12270-4859 and PSR J1824-2452I (M28I), suggesting that radiatively inefficient accretion may be a ubiquitous phenomenon among (at least one class of) neutron star binaries at low accretion rates.